The Influence of Knowledge about Anemia, Dates, and Iron Tablets on Hemoglobin Levels in Prospective Pregnant Women at South Klaten Community Health Center - Yulaikah, Siti; Kuswati, Kuswati (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: Anemia, commonly known as a deficiency in blood, influences individual behavior. Higher knowledge about anemia before conception correlates with a greater awareness of nutritional needs. Preventing anemia in preconception women involves iron tablet consumption, while dates serve as an alternative means to prevent anemia. This study aims to ascertain the influence of anemia knowledge, date consumption, and iron tablet intake on hemoglobin levels among prospective pregnant women at the Klaten Selatan Community Health Center. This research heald on January to September 2023 in the operational area of the Klaten Selatan Community Health Center. Methods: This research adopts a pre-experimental design employing a one- group pretest-posttest study. Purposive Random Sampling method is used, encompassing 40 research subjects. The dependent variable is hemoglobin levels, while the independent variables are knowledge about anemia, date consumption, and iron tablets. Data collection involves primary data through questionnaire responses and observation sheets. Research analysis includes univariate analysis, bivariate analysis utilizing the Spearman Rho test for knowledge variables and the Friedman test for date and iron tablet consumption variables. Results: There is a significant impact of knowledge about anemia (p = 0.000), date consumption (p = 0.0094), and iron tablet intake (p = 0.0073) on hemoglobin levels among prospective pregnant women. Conclusion: Knowledge about anemia influences hemoglobin levels, and there is an increase in hemoglobin levels after consuming dates and iron tablets among prospective pregnant women at the Klaten Selatan Community Health Center.